Co-design of a walking activity intervention for stroke survivors - H. Wittink; C. van Gessel; J. Outermans; T. Blatter; M. Punt; R. van der Lugt (Frontiers Media S.A., 2024)
IntroductionStroke survivors may not maintain gains made in gait performance after task-oriented circuit training. Behavior change interventions may enhance the long-term adoption of physical activity. This study uses a co-design methodology to develop an intervention and tools to facilitate physical and exercise therapists in supporting an active lifestyle in stroke survivors, which is defined as a lifestyle that integrates daily walking performance with day-to-day activity.Objectives(1) To describe the insights generated during the co-design process; and (2) To describe the tools that were developed during the co-design process.MethodsA multidisciplinary team consisting of staff members of the Royal Dutch Society for Physical Therapy, exercise and physical therapists specializing in neurorehabilitation and conducting task-oriented circuit class training in primary care settings or day therapy centers within residential care facilities, stroke survivors and their carers, experts in measuring movement behavior in stroke survivors, a company specializing in manufacturing sensors and related software, behavior change specialists, and co-designers all collaborated in a three-stage (define, develop, and deliver) co-design process.ResultsIn the design process, the team iteratively developed a prototype accelerometer system for measuring walking performance with a feedback function for stroke survivors and their therapists and a prototype toolbox for therapists to support the facilitation of behavior change in their stroke survivors.DiscussionThis study shows how co-design can be applied to develop interventions for stroke survivors. Both the prototype system for measuring walking performance and the toolbox incorporate behavior change techniques to support a more physically active lifestyle in stroke survivors. Further research will investigate the feasibility of the intervention.